Correlation of Hematological Profiles and Parasite Density of Malaria Patients from Low Endemic Areas in North Sulawesi, Indonesia - Senduk, Evy Beatrix; Tuda, Josef Sem Berth; Kurniawan, Agnes; Diptyanusa, Ajib (Faculty of Medicine Universitas Indonesia, 2025)
North Sulawesi province is an area with low malaria endemicity. Variations in hematological profiles of malaria patients can serve as indicators for malaria diagnosis. This study aimed to determine correlation of hematological profile and parasite density of malaria patients. The cross-sectional study utilized medical record data from Kandou Hospital, Budi Mulia Hospital, and Tuda Hospital in North Sulawesi Province. The study was conducted from October 2022 to June 2023. In the current study, a total of 65 patient medical records were analyzed. Among them, 28 patients (43.1%) were infected with Plasmodium falciparum, and 37 patients (56.9%) were infected with P. vivax, with 20% of cases belonged to age group of <12 years. Hematological profiles showed moderate to severe thrombocytopenia in falciparum malaria cases and mild to severe thrombocytopenia in vivax malaria cases, while normal leukocyte count was observed in the majority of cases in both groups. Sex (p=0.014) and thrombocytopenia (p=0.034) showed a statistically significant association with malaria infections in this study. Anemia, thrombocytopenia and leukocyte counts did not show a statistically significant association with the degree of parasitemia in patients with falciparum and vivax malaria (r <0.40; p >0.05). The results of current study can be used as additional predictive variables for patients suspected of having malaria in similar populations.